Variation in the composition of breast milk during the first 5 weeks of lactation: implications for the feeding of preterm infants. Issue 9 (September 1982) - Hibberd, C M; Brooke, O G; Carter, N D; Haug, M; Harzer, G
Abstract : Milk samples were collected from 10 mothers by a standardised technique with complete expression of both breasts at each feed for 24 hours. Samples were obtained at 8 intervals during the first 36 days of lactation. Analyses were performed for trichloroacetic acid-precipitable protein, total protein, lactose, triglycerides, phospholipids, cholesterol, energy, sodium, potassium, calcium, magnesium, zinc, copper, pH, and osmolality. The results give a comprehensive picture of the development of milk composition from transitional to mature milk. The most striking feature of the results was the high degree of variation observed both between samples from the same mother and between samples from different mothers on the same day of lactation.